Religious Authority in the Digital Age: A Critical Discourse Analysis of Islamic Debates on Music in Indonesia - Ghozi, Tsabituddin Al; Zamzami, Mukhammad; Lutfi, Muhammad; Hegazy, Wael (FIKRAH, 2025)
The debate over non-religious music in Islam reflects an epistemological polarization in Indonesia's digital space, represented by Yufid TV and Bincang Syariah. Yufid TV based on a literal Salafi interpretation, rejecting music by referring to the Islamic doctrine of the hadith. This study aims to investigate how Islamic authority is negotiated through discourse on non-religious music across two prominent digital platforms, Yufid TV and Bincang Syariah.com. Methodologically, it employs Norman Fairclough’s Critical Discourse Analysis (CDA) to examine the textual, discursive, and socio-cultural dimensions of how both platforms construct, disseminate, and legitimize religious interpretation within the digital public sphere. The findings reveal that Yufid TV constructs a puritan discourse grounded in literalist interpretation, portraying music as a deviation from the purity of Islamic teachings. In contrast, Bincang Syariah adopts a contextual and maqaṣid-oriented approach, framing music as an ethical and cultural expression. Audience responses demonstrate a significant epistemological polarization, reflecting the broader transformation of religious authority from traditional institutions to digital spaces. Academically, this article contributes to contemporary Islamic studies by bridging discourse analysis and digital religion research, highlighting how online media functions as a new arena for ijtihad and the negotiation of religious legitimacy within modern Muslim societies